PERCEPTION OF USER EXPERIENCE: CASH AND BANK LEARNING VIDEO IN INTRODUCTORY ACCOUNTING COURSE AT DIPLOMA4 LEVEL - Tri Septianto; Koerniawan Dwi Wibawa; Angga Lisdiyanto (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2023)
Many changes have occurred due to the digitalization of education in Indonesia today, especially in terms of teaching and learning. Many colleges and universities have incorporated digital technology into the educational process, one of which is learning videos. Learning videos can be in the form of class recordings that are uploaded to the internet or tutorial videos made specifically for certain subjects. Learning videos can help students understand material more easily and can be accessed by students anytime and anywhere, thus facilitating the teaching and learning process. User Experience (UX) deals with the emotions, feelings, and thoughts that users experience when using a product or service. UX can be applied to learning videos by focusing on several factors, such as delivering material that is clear and easy to understand. So in this study, a UX assessment was carried out on learning videos. Learning videos using cash and bank material in introductory accounting courses at the diploma level with the concept of motion graphics Motion graphics were chosen because of their flexibility in conveying this information and attracting students' interest. This study consisted of seven processes, including: 1) determining goals and objectives; 2) making scenarios and scripts; 3) equipment preparation; 4) recording; 5) editing; 6) publication; and 7) assessment. In the assessment process, the respondent fills out a questionnaire. The questionnaire consists of 10 questions with aspects of use (usefulness, satisfaction, and ease of use). The value of each question in the questionnaire ranges from 1 to 4, with the following conditions: 1) bad; 2) enough; 3) good; and 4) very good. Every day for seven days, ten different people responded. As a result of filling out the questionnaire, a fluctuating curve was obtained.